2020
DOI: 10.1016/j.compag.2020.105233
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning to detect behavioural anomalies in dairy cows under subacute ruminal acidosis

Abstract: et al.. Machine learning to detect behavioural anomalies in dairy cows under subacute ruminal acidosis. A B S T R A C TSickness behaviour is characterised by a lethargic state during which the animal reduces its activity, sleeps more and at times when normally awake, reduces its feed and water intake, and interacts less with its environment. Subtle modifications in behaviour can materialise just before clinical signs of a disease. Recent sensor developments enable continuous monitoring of animal behaviour, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 26 publications
0
34
0
1
Order By: Relevance
“…Attempts to detect subacute ruminal acidosis by analyzing behavioral anomalies with ML algorithms have failed [ 57 ]. Although it was possible to detect 83% of cases using k -nearest neighbor regression, the results were not useful in practice due to a false positive rate of 66% [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Attempts to detect subacute ruminal acidosis by analyzing behavioral anomalies with ML algorithms have failed [ 57 ]. Although it was possible to detect 83% of cases using k -nearest neighbor regression, the results were not useful in practice due to a false positive rate of 66% [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Particularly, rumination and feeding behavior are possible indicators for improving dairy cow management. Wagner et al [ 57 ] evaluated whether ML algorithms could be useful to predict subacute ruminal acidosis from positioning data that reflect cows’ activity. They reported that, among the tested ML algorithms, k -nearest neighbor performed best, with 83% true positives; unfortunately, the false positive alert rate was 66%.…”
Section: Resultsmentioning
confidence: 99%
“…Machine Learning approaches have been heavily used in animal behavioural/disease assessment over the last few years. Take as an example [29], where the authors applied different methods for detection of subacute ruminal acidosis in dairy cows. In their results, k-Nearest Neighbors showed the best results, outperforming deep learning methods and decision trees.…”
Section: Machine Learning In Animal Disease Detectionmentioning
confidence: 99%
“…Advances in image analysis now allow automated recognition of individuals within a herd (Andrew et al, 2020), and accurate identification of health-related abnormal behaviors, such as foot disease (Gu et al, 2017). The identification of behaviors associated with subclinical disease (before the development of, or without, clinical symptoms) may therefore find application in future diagnostic software algorithms targeted at early disease monitoring in dairy cows (e.g., Wagner et al, 2020).…”
Section: Introductionmentioning
confidence: 99%